Case Report: Vascular access in paediatric haemodialysis patients—creating and maintaining the patency of an arteriovenous fistula - Ramona Stroescu; Ramona Stroescu; Serban Comsa; Serban Comsa; Flavia Chisavu; Flavia Chisavu; Flavia Chisavu; Mihai Gafencu; Mihai Gafencu (Frontiers in Surgery, 2024)
IntroductionPaediatric vascular access is a demanding field. The need for a multidisciplinary team is mandatory in children with end-stage kidney disease (ESKD). Central venous catheters (CVCs) remain the preferred option worldwide. Recent emerging data demonstrated the benefits of using arteriovenous fistulas (AVFs) in the paediatric population for long-term vascular access. The small vessel size in children represents a surgical challenge for vascular access.Case presentationWe report three cases from our haemodialysis department and the difficulty in maintaining permanent vascular access. The first case is an adolescent girl who required a change in vascular approach after multiple central venous catheter (CVC) infections and catheter thrombosis secondary to thrombophilia. Three AVFs were performed but failure occurred early. The patient was also diagnosed with a complex vascular thrombosis with total occlusion of the inferior vena cava and completed distal thrombosis of the superior vena cava. A permanent CVC was placed in the right jugular vein with the tip in the azygos vein. The second case is of an adolescent boy with systemic vasculitis with multiple CVC infections secondary to immunosuppression. The first thrombosis of two right AVFs occurred early with the development of a pseudo-aneurysm that required surgical intervention. The left brachial-cephalic fistula required surgery for closing the collaterals, repositioning and superficialisation. The third case is an adolescent boy with one surgical stage brachial-basilic left AVF and difficulties in venous puncturing.ConclusionVascular access in paediatric haemodialysis remains a demanding field. There is a need for a multidisciplinary team, consisting of a vascular surgeon and an interventional radiologist specialising in children.